2022
DOI: 10.1038/s41598-022-12252-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-nucleocapsid antibodies enhance the production of IL-6 induced by SARS-CoV-2 N protein

Abstract: A cytokine storm induces acute respiratory distress syndrome, the main cause of death in coronavirus disease 2019 (COVID-19) patients. However, the detailed mechanisms of cytokine induction due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remain unclear. To examine the cytokine production in COVID-19, we mimicked the disease in SARS-CoV-2-infected alveoli by adding the lysate of SARS-CoV-2-infected cells to cultured macrophages or induced pluripotent stem cell-derived myeloid cells. The cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 70 publications
2
22
0
Order By: Relevance
“…Therefore, the comparison of correlation between cytokines and antibody response in the infected group and the vaccinated group can imply the future role of cytokine supplements on vaccine development. In another study, increased IL‐6 in COVID‐19 patients with severe diseases has been reported to be associated with SARS‐CoV‐2 N protein 41 . It may be correlated with the stronger immune response in the infected individuals.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, the comparison of correlation between cytokines and antibody response in the infected group and the vaccinated group can imply the future role of cytokine supplements on vaccine development. In another study, increased IL‐6 in COVID‐19 patients with severe diseases has been reported to be associated with SARS‐CoV‐2 N protein 41 . It may be correlated with the stronger immune response in the infected individuals.…”
Section: Discussionmentioning
confidence: 89%
“…[29][30][31] Clinical factors were also verified to influence antibody levels in with severe diseases has been reported to be associated with SARS-CoV-2 N protein. 41 It may be correlated with the stronger immune response in the infected individuals. Accordingly, the influence of cytokines on vaccine outcomes should be considered in the future of vaccine development.…”
Section: Different Expression Of Cytokines Between Previously Infecte...mentioning
confidence: 99%
“… 41 43 The repercussion(s) of the lack of anti-N antibodies is unclear, but has recently been suggested to be important for IL6 production and possibly cytokine storm induction. 44 Investigating these possibilities was beyond the scope of our current study but warrants further investigation. Since antibodies against N protein are often used to confirm past infection, our current finding has important implications on the utility of existing serological diagnostic and surveillance for SARS-CoV-2 prevalence in breakthrough infections.…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, there is substantial evidence that anti-S antibodies are crucial in the recovery from COVID-19 [ 23 , 25 , 26 , 28 ]. There is even evidence that anti-N antibodies might contribute to the pathogenesis of the cytokine storm in COVID-19 [ 33 ]. Therefore, we focused on anti-S antibody response and utilised just the test to assess the presence of anti-S antibodies.…”
Section: Discussionmentioning
confidence: 99%